HUBUNGAN DINAMIS VARIABEL MAKROEKONOMI DAN PERTUMBUHAN SUKUK NEGARA, PENDEKATAN: ERROR CORECTION MODEL - Teuku Ghufran Wafi; Muhammad Zulhilmi; Winny Dian Safitri; Cut Dian Fitri (Universitas Teuku Umar, 2020)
This study aims to examine the effect of PBD, Exchange Rate, Inflation, Profit Sharing Sharia Deposits, World Oil Prices, SBIS on the growth of state sukuk. Sukuk is one of the important instruments in financing fiscal deficits. So far, tax and non-tax state revenues have not been able to finance all government spending. Government expenditure is intended to encourage economic growth and equitable distribution of public income. However, spending in 2020 is more aimed at handling Covid-19 that hit Indonesia, especially on health programs and social security. This study uses secondary data in the form of monthly time series (from January 2014 to December 2019). A number of variables are used to see the effect of balance in the short and long run between the independent variables and the dependent variable. Data obtained from government agencies, including: Financial Services Authority (OJK), Central Statistics Agency (BPS) and Directorate General of Debt Utilities Ministry of Finance of the Republic of Indonesia (DJPU). The econometric analysis model Error Correction Model (ECM) is used to see the effect between the two. From the research results obtained, GDP, BHDS and SBIS have a positive effect on the growth of Sukuk. While inflation and oil prices have a negative effect on the growth of sukuk. Keywords: Macroeconomic Variables, BHDS, SBIS, Sukuk Negara, ECM